Mixed Fortunes: Prices paid to soybean farmers have improved in 2021…but not those to maize farmers - Baulch, Bob; Jolex, Aubrey (International Food Policy Research Institute, 2021)
Between April and July 2021, IFPRI Malawi conducted its second, nationwide crowdsourcing exercise on the maize and soybean prices paid to farmers. In contrast, to the main harvesting season in 2020, when around three-quarters of sales of maize and soybeans took place at less than the official minimum farmgate price (MFGP), in 2021 the prices paid to soybean farmers have been good but those paid to maize sellers have been poor. Specifically, between early April and late June this year, about eighty percent of soybean farmers received prices equal to or above the minimum price for soybean. However, over the same period, less than ten percent of maize farmers received prices equal to or above the MFGP for maize.